Lokakarya Kurikulum Merdeka Dalam Upaya Meningkatkan Implementasi Merdeka Belajar Kepada Guru Sd It Bahrul Uluum Kec. Wedi Kab. Klaten - Khasanah, Sabtun Ismi; Nurdin, Akhmad; Lutiyatmi, Lutiyatmi; Suparni, Suparni; Sidiq, Rustam; Wahid, Nur (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
Educational transformation is a change in the education system to adapt to changing times and future needs. The independent curriculum policy encourages educational transformation towards independent learning. The independent curriculum policy is followed by several programs that support the implementation of the independent curriculum, including the driving school program. The driving school is a program where schools become role model projects for implementing the independent curriculum. SD IT Bahrul Uluum is currently not a driving school. In implementing the independent curriculum, SD IT Bahrul Uluum is classified as a type of school that implements the independent independent learning curriculum. As a non-PSP school, the principal and teachers of SD IT Bahrul Uluum are lacking in implementing the independent curriculum both from the cognitive (literacy and numeracy) and non-cognitive (character) aspects, in order to realize the profile of Pancasila students. In addition, the principal and teachers have not optimally utilized digital information technology or school digitalization to encourage educational transformation. This community service program is carried out to improve the competence of principals and teachers in implementing the independent curriculum and to increase the capacity of teachers in utilizing school digitalization. This program has been done through intensive training and mentoring for principals and teachers of SDIT Bahrul Uluum. Through this activity, principals and teachers better understand the independent curriculum material so that it can later be implemented in schools and each class. By increasing teacher competence in implementing the independent curriculum, learning will be more meaningful and have an impact on students. Through this activity, principals and teachers can better utilize the Education platform so that they can support principals and teachers in implementing the independent curriculum.